2018
DOI: 10.1542/peds.2017-4276
|View full text |Cite
|
Sign up to set email alerts
|

Language Experience in the Second Year of Life and Language Outcomes in Late Childhood

Abstract: These data support the hypothesis that early talk and interaction, particularly during the relatively narrow developmental window of 18 to 24 months of age, can be used to predict school-age language and cognitive outcomes. With these findings, we underscore the need for effective early intervention programs that support parents in creating an optimal early language learning environment in the home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
240
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(290 citation statements)
references
References 29 publications
22
240
2
5
Order By: Relevance
“…These findings have important implications for interventions that aim to reduce the word gap, suggesting services with this specific aim may need to utilize a universal approach, rather than simply targeting families from low socioeconomic *p-value is based on independent sample t-tests comparing the means between high and low educated groups backgrounds, as it is clear from our data there are adults across both socioeconomic groups who would be considered low talkers. While our data cannot yet explain if the amount families talk to their children in the home will lead to differences in future development outcomes, previous research has suggested this is the case [8,21,22]. As the LiLO study progresses, it will describe the trajectories of AWC, CVC and CT's for low and high maternal education groups and consequences for child development outcomes over the first five years of life.…”
Section: Discussionmentioning
confidence: 83%
“…These findings have important implications for interventions that aim to reduce the word gap, suggesting services with this specific aim may need to utilize a universal approach, rather than simply targeting families from low socioeconomic *p-value is based on independent sample t-tests comparing the means between high and low educated groups backgrounds, as it is clear from our data there are adults across both socioeconomic groups who would be considered low talkers. While our data cannot yet explain if the amount families talk to their children in the home will lead to differences in future development outcomes, previous research has suggested this is the case [8,21,22]. As the LiLO study progresses, it will describe the trajectories of AWC, CVC and CT's for low and high maternal education groups and consequences for child development outcomes over the first five years of life.…”
Section: Discussionmentioning
confidence: 83%
“…Language is a pivotal function, important for developing social relationships and achieving academic success. Some authors have hypothesised that language exposure in early infancy, in terms of vocabulary quantity and quality, is particularly important because it mediates the relationship between the family socioeconomic environment and neurodevelopment in childhood 8. There is evidence that language functioning is reduced in school-aged children born VPT compared with term controls 9–11.…”
Section: Introductionmentioning
confidence: 99%
“…Although the emphasis of the word gap has historically been on adult words directed at children, adult–child conversational turns have been found to be more predictive of children’s language development than adult words (Gilkerson et al, ). Thus, much of the emphasis of this commentary can also be applied to adult–child conversational turns.…”
Section: Why Is a More Precise Estimate Of The Word Gap (Or Lack Thermentioning
confidence: 99%